Experimental study on the solar heating and night sky radiative cooling properties of biochar - Haiwei Xie; Jianyun Luo; Yan Zhang; Jiajuan Yan; Yuhao Qing (Case Studies in Thermal Engineering)
Daytime solar heating and nighttime radiative cooling are of great significance to global energy conservation and carbon neutrality because of their low cost, zero energy consumption and environmentally friendly characteristics. In this study, a new radiation material, walnut shell biochar (WBS), was proposed and its performance in daytime solar heating and nighttime radiative cooling was studied. The experimental results indicate that WBS exhibits a maximum absorption rate of 95.93 % within the solar radiation spectrum, along with an average emissivity of 92.45 % in the atmospheric transmission window. When utilizing a low-density polyethylene film cover plate with a thickness of 10 μm and employing 50 mesh of WBS, the combined effect of daytime solar heating and nighttime radiative cooling is optimized. Under conditions where the solar radiation intensity reaches 750 W/m2, the surface temperature of WBS is observed to be 63.3 °C higher than that of the ambient temperature. Conversely, on clear nights, this surface temperature drops to be 15.5 °C lower than that of its surroundings. This research provides valuable technical support for developing integrated processes that leverage both daytime heating and nighttime radiative cooling.